Counseling on the Recycling of Used Goods to Mts Students in Bekasi, West Java - Cleopatra, Maria; Sahrazad, Sarah; Suprapto, Hugo Aries; Sandiar, Loecita; Ati, Aster Pujaning; Widiyarto, Sigit; Sanjawati, Arum (Jurnal Pengabdian Masyarakat Bestari, 2024)
This activity aims to provide education to Mts students, recycling used goods to keep the school clean. Activities will be carried out from January to March 2022 at Mts Nurul Hikmah Bekasi. The activity was attended by 31 class VII students. The activity method is carried out through counseling, theory and practice of recycling used goods into useful items such as pencil cases and tissue holders. The activity ends with an evaluation. A total of 21 students got good grades and the rest still need treatment and improvement in practice.